Kematangan Beragama sebagai Referensi Muslim dalam Menghadapi Pandemi Covid-19: Studi Perspektif Quraish Shihab - Lia Caswati (ICODEV: Indonesian Community Development Journal, 2021)
In the context of the Covid-19 pandemic, health experts recommend various steps to prevent its spread, such as readiness, physical and mental resilience. Religious scholars recommend for Muslims to increase their prayers to strengthening their mentality and spirituality. Religion is a reference in attitude and behavior to be in line with the beliefs held. Al-Qur’an and Hadith as the basis of the Muslims provide instructions for dealing with diseases or viruses. Seeing the various responses and attitudes of the community towards Covid-19, this article aims to discuss religious maturity during the Covid-19 pandemic by looking at the perspective of Quraish Shihab. This study used the descriptive qualitative method. The primary material in this study is a documentary video sourced from interview coverage, national television news, and content on Najwa Shihab’s Youtube Channel. The results showed that Quraish Shihab had a high religious maturity perspective that could be a reference in dealing with the Covid-19 pandemic by the Muslim community.